Guía práctica de convivencia para familiares de adolescentes que presentan el Trastorno Bipolar - Del Valle Carro, Paula (2012)
Bipolar Disorder involves emotional, behavioral and cognitive changes which range from two extremes, mania and depression. These poles are called episodes and can occur in different intensity, duration and repetition. The manic episodes are characterized by euphoria, increased energy, irritability, inattention, among others. Depressive episodes are associated with sadness, fatigue, feelings of inner emptiness and even suicidal thoughts. This disorder is quite complex in the everyday; complicating family life especially when is a teenager who presents it. This manual includes a literature review focused on providing, in simple language, multiple cognitive and practical tools for families of adolescents with this disorder. First it provides an explanation of the disorder and possible symptoms, as well as tools with which family members can support the adolescent to handle the intensity, duration and even presence of different episodes, for example in sports, sleeping well, eating right, among others. Finally, it describes the importance of self-care by relatives of people with this disorder.